Cost-of-Illness Analysis of Type 2 Diabetes Mellitus in the Russian Federation: Results from Russian multicenter observational pharmacoepidemiologic study of diabetes care for patients with type 2 diabetes mellitus (FORSIGHT-Т2DM) - Ivan I. Dedov; Marina F. Kalashnikova; Dmitriy Y. Belousov; Aleksey S. Kolbin; Vladimir V. Rafalskiy; Aleksey E. Cheberda; Mariya A. Kantemirova; Vadim D. Zakiev; Valentin V. Fadeyev (Сахарный диабет)
Background: Cost-of-Illness Analysis (COI) constitutes the basis for the decision-making process on the budget and allocation in a modern health care system. Considering the wide prevalence of type 2 diabetes mellitus (Т2DM), it is important to perform COI in the Russian Federation (RF). Aim: The aim of the secondary objective FORSIGHT-Т2DM study was to conduct Cost-of-Illness Analysis (COI) of Т2DM in the Russian Federation in relation to taking into consideration the presence of complications and concomitant diseases. Materials and methods: COI of Т2DM was performed using the data obtained in Russian multicenter observational, pharmacoepidemiologic cross-sectional study of diabetes care for assessing routine healthcare pattern of T2DM in the Russian Federation (FORSIGHT-Т2DM). Information for each patient was collected from primary medical records and By asking patients to fill out a questionnaire. Total costs were calculated as the sum of direct medical costs (DCm), direct non-medical costs (DCn) and indirect costs (IC). Results: The final analysis included data from 2014 patients with T2DM residing in 45 cities of RF. Total direct medical costs (DCm) of treating Т2DM and its complications and comorbidities amounted to 105 337 rubles ($2742) per patient per year; direct non-medical costs (DCn) amounted to 24 518 rubles ($638) per patient per year; indirect costs (IC) amounted to 149 754 rubles ($3898) per patient per year. The total cost of T2DM in RF in 2014 year amounted to 279 609 rubles ($7278) per patient. The total cost of T2DM in RF in 2014 amounted to 279 609 rubles per patient. Conclusions: More than half (53,5%) of the total cost of T2DM is the loss of GDP due to patients’ disability. The DCm constitute 37,7% of the total cost of the disease, of which 57% is spent on treatment of T2DM complications and concomitant diseases, while only 10% is spent on glucose-lowering therapies.